Knowledge And Attitude Regarding Tobacco and Its Use Among Adolescent Students - Kirthinath Ballal; Muralidhar Kulkarni; Ayushi Agrawal; Asha Kamath; Muthu Kumar (Medsci Publications, 2016)
Introduction: Tobacco consumption is one of the leading causes of morbidity and mortality all over the world. This habit is increas- ingly being taken up at an early age. Various factors have been implicated for the uptake of the habit including inadequate knowledge and unfavorable attitude. Methodology: A cross-sectional study was conducted in urban schools in a town, located in South-west Karnataka. The students belonged to 8th and 9th grade and were aged between 13 to 15 years. A self-administered questionnaire adapted from Global Youth Tobacco Survey (GYTS) was used for the study.. Result: A total of 1271 students participated in the study with equal participation from boys and girls. The mean knowledge score for the study participants was 14.57 ± 4.0. Approximately 36% of the students had poor knowledge and was significantly less in females compared to males. The knowledge score was signifi- cantly different with respect to parent's occupation, their favorable or unfavorable attitude towards not using tobacco products and presence of a smoking family member. Conclusion: In spite of several measures taken to improve the knowledge regarding tobacco hazards and laws among the ado- lescents, there are various barriers which need to be addressed for effectiveness of these interventions.